The Innovation for the Development of Ceria Park Tourism Objects in Warangan Village to Increase Local Tourist Attraction: Inovasi Pengembangan Objek Wisata Taman Ceria Di Desa Warangan Untuk Meningkatkan Daya Tarik Wisatawan Lokal - Asep Sunarko; Ambiya, Sri winduri; Mar Atul Ma’rifah; Irwan Budi Santoso; Ihda Noor Mujib (CV. Nature Creative Innovation, 2023)
To improve local tourist attraction, an innovative development of cheerful garden attractions in Warangan villages was undertaken. The development of those who seek to privatize aims to make those available in terms of quality tools and infrastructure, making destinations more accessible and desirable, as well as the character and income of those around them. The goal of the study was to create a cheerful garden tour in the Warangan village. The method employed is field research, which describes the development and research of cheerful-age tourist attractions in the village of Kepil district Warangan, and the second is to include a description of the drives and obstacles in the development of cheerful garden attractions. The recommended proposal that can be used to achieve the goal of developing tourist attractions in a fun park is to educate the tourist authority on the importance of preserving the urgent tourist attraction that impedes the expansion of tourism needed to accommodate the promotion specifically targeting investors and creating innovation that can boost tourist attraction.Key words: Innovation, development, and local tourist attraction